THE STATE OF STUDY OF THE VOKHCHABERD LANDSLIDE: (Kotayk Region, Armenia) (Proceedings of the YSU C: Geological and Geographical Sciences, 2024)
The Vokhchaberd landslide is one of several large seismogravitational landslides confined to the zone of the seismically active Garni fault. It is a block in size from 2.5–2.8 km2 and an estimated average thickness of 70–80 m, torn off the steep slope of the ridge of the same name and shifted along the fault line of an upsurge character. To date, there is a certain amount of factual material on the Vokhchaberd landslide (its origin, a number of external parameters, the nature of activity, the position of groundwater, the destruction of rural buildings and highways caused by it, etc.). However, there is no reliable data on the thickness of the landslide, which does not allow to determine the most suitable landslide measures for this area. Capital measures are required to completely stop the displacement of the landslide layer. To determine the thickness of the landslide, it is necessary to drill at least 3 wells along its length, but be sure to drill to the sliding surface.
Keywords: Vokhchaberd; seismogravitational landslide; thickness; sliding surface